2008
DOI: 10.1016/j.neuropharm.2007.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor-mediated translocation of NO-sensitive guanylyl cyclase and production of cyclic GMP in neuronal cells

Abstract: Cannabinoid agonists regulate NO and cyclic AMP production in N18TG2 neuroblastoma cells, leading to the hypothesis that neuronal cyclic GMP production could be regulated by CB(1) cannabinoid receptors. NO (nitric oxide)-sensitive guanylyl cyclase (GC) is a heterodimeric cytosolic protein that mediates the down-stream effects of NO. Genes of proteins in the cyclic GMP pathway (alpha(1), alpha(2), and beta(1) subunits of NO-sensitive GC and PKG1, but not PKG2) were expressed in N18TG2 cells, as was the CB(1) bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…‫,ء‬ P Ͻ 0.05 versus vehicle. , 2007Chan et al, 2003Chan et al, , 2004Ally et al, 2007;Mayorov, 2007;Guo et al, 2009)]; and 2) many of the CB 1 R-mediated neurobiological responses depend on nNOS/NO signaling (Makara et al, 2007;Jones et al, 2008;Carney et al, 2009). Here, we present the first evidence that early (5 min) activation (phosphorylation) of RVLM nNOS (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…‫,ء‬ P Ͻ 0.05 versus vehicle. , 2007Chan et al, 2003Chan et al, , 2004Ally et al, 2007;Mayorov, 2007;Guo et al, 2009)]; and 2) many of the CB 1 R-mediated neurobiological responses depend on nNOS/NO signaling (Makara et al, 2007;Jones et al, 2008;Carney et al, 2009). Here, we present the first evidence that early (5 min) activation (phosphorylation) of RVLM nNOS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced phosphorylation of nNOS, which leads to NO release, underlies a wide array of CB 1 R-mediated neuropharmacological actions (Azad et al, 2001;Makara et al, 2007;Jones et al, 2008;Carney et al, 2009). For example, CB 1 R activation in CA1 hippocampal pyramidal neurons leads to nNOS-NO-dependent suppression of GABAergic neurotransmission (Makara et al, 2007); further, nNOS-derived NO in the brainstem is involved in central blood pressure regulation (Martins-Pinge et al, 1999, 2007Mayorov, 2007;Nassar and Abdel-Rahman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of an adenosine A 1 receptor-mediated effect on SNPstimulated cGMP accumulation in females suggests that adenosine A 1 receptor stimulation of sGC not mediated by NO increase, could also be operating in females -in fact, non nitric oxide-mediated mechanisms for sGC activation have been described (Agulló et al, 2005;Jones et al, 2008). The possibility that this effect of adenosine A 1 receptor in females results from activation of pGC seems unlikely, since increasing total cGMP levels through NO-mediated activation of sGC by SNP, would reduce the adenosine A 1 receptor-induced relative increase of cGMP accumulation if this increase was mediated by pGC activation.…”
Section: Nitric Oxide and Gender Dependence Of The Adenosine A 1 Recementioning
confidence: 99%
“…Using the N18TG2 neuroblastoma model, we have found that cannabinoid agonists CP55940 and WIN55212-2 cause a translocation of the soluble guanylyl cyclase from the cytosol to the membrane fraction (Jones et al 2006). This response can be blocked by rimonabant as well as by pertussis toxin, indicating that the CB 1 receptor-Gi/o signal transduction pathway is involved.…”
Section: Reactive Nitrogen Speciesmentioning
confidence: 99%